Metaphors in Selected Lyrics on Taylor Swift's Album "Folklore": A Semiotics Approach - Inayah, Nisrina Zakia; Amalia, Syahara Dina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to analyze the selected lyrics from Taylor Swift's album "folklore." The data for this study was obtained from the ten most frequently listened-to songs (YouTube, 2020). The primary objective is to identify various metaphors and explore the semiotic meanings within the denotative and connotative of the selected lyrics. This descriptive qualitative research employs data collection through reading and listening analysis of song lyrics, focusing on the identification of metaphors and their meanings. Following the approach outlined by Miles and Huberman (1994), the data analysis involves data reduction, data perspective, and verification. The researchers categorized the metaphors identified in the lyrics into three groups: structural, orientational, and ontological metaphors. Utilizing structural metaphors facilitates the comprehension and expression of one idea in terms of another, ensuring a well-defined and organized conceptual framework. Orientational metaphors do not structure one concept in terms of another but instead organize "a whole system with respect to one another." An ontological metaphor is a way of describing abstract or difficult ideas by relating them to more familiar and tangible contexts. The kind of metaphor that is most frequently found in certain songs is the structural metaphor. Next, the meanings of 21 chosen song lyrics are examined using the denotation and connotation meaning. A sign is said to be denotative if there is a high degree of agreement between its signifier and actual meaning. Roland Barthes defined connotation as a system consisting of signifier, signified, and the action that connects the first to the second.